Design parameters justification of the plough bottom’s landside - Nadykto, Volodymyr; Horetska, Iryna; Kyurchev, Volodymyr; Golub, Gennadii; Kielbasa, Pawel; Pidlisnyj, Vitaliy; Hutsol, Taras; Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович (SGGW : Nature portfolio, 2025)
EN: The use of a plough is characterized by the presence of a turning moment acting in a clockwise direction. When placing the plough resistance center to the left of the tractor’s longitudinal symmetry axis, it becomes possible to use the plough with one landside placed on its last bottom. The article presents a new analytical dependence that allows determining the design and technological parameters of the plow using the transverse displacement of the center of resistance to the left of the tractor’s longitudinal axis of symmetry. Studies have shown that using a plough with one landside instead of five does not affect the ploughing depth and the operating width. At the statistical significance level of 0.05, the null hypothesis about the equality of the mean values and variances of these parameters’ oscillations is not rejected. The normalized correlation functions and spectral densities of these processes’ oscillations are approximately the same. Using a plough with one landside instead of five leads to a 10.3% decrease in draft resistance, accompanied by a 10% decrease in specific fuel consumption. This study fills a gap in the practical operation of plows, aimed at reducing their draft resistance, which is key in reducing fuel consumption.
Keywords: width of landside; length of landside; turning moment; ploughing depth; plough operating width; plough draft resistance; ширина відвала плуга; довжина відвала плуга; момент обертання; глибина оранки; робоча ширина плуга; сила тяги плуга